Influence of temperature and water activity on growth and aflatoxin production of Aspergillus flavus strains isolated from chickpeas - Romero Donato, Cindy Johana (2022)
Chickpea (Cicer arietinum L.) is one of the most cultivated pulses in terms of world production. There is a high demand for world production due to the crops nutritional value. In Argentina, most of chickpea production is exported. Chickpea is susceptible to more than 25 well documented fungal pathogens, that cause seed deterioration, and contamination with mycotoxins. The most worldwide prevalent fungi in chickpeas are species belonging to Aspergillus, Fusarium, Penicillium, Alternaria, and Rhizopus genera. In a previous study we observed that A. flavus was the prevalent fungi isolated from chickpea. Considering that A. flavus has the ability to produce aflatoxins (compounds classified in group 1 by IARC) and aflatoxin production and fungal growth of A. flavus can be influenced by abiotic conditions, the effect of water activity (aW; 0.99, 0.98, 0.96, 0.94, 0.92, 0.90 and 0.87), temperature (15, 25, and 30 °C), incubation time (5, 10, 14, and 21 days), and their interactions on mycelial growth and aflatoxin production in a chickpea-based medium by three A. flavus strains isolated from chickpea in Argentina was evaluated. Maximum growth rates were obtained at aW 0.99 and 30 °C, with growth decreasing as the aW of the medium was reduced. Maximum amounts of aflatoxins were produced at 0.99 aW and 25 °C after 5 days of incubation for 2 strains, and at 25 °C and 0.96 aW after 21 days of incubation for the third strain. Aflatoxin concentrations varied depending on the aW and temperature interactions assayed. Two-dimensional profiles of aW by temperature interactions were developed from these data to identify areas where conditions indicate a significant risk from aflatoxin accumulation on chickpea. This study provides useful data about conditions representing a high and a low risk for aflatoxin contamination of chickpea which is of greater concern because chickpea is destined mainly for human consumption.